Hyper-réflexivité et perspective en première personne: un apport décisif de la psychopathologie phénoménologique contemporaine à la compréhension de la schizophrénie = Hyper-reflexivity and the first-person perspective: A decisive contribution of contemporary phenomenological psychopathology to the understanding of schizophrenia - Englebert, Jérôme; Fuchs, Thomas (L' Évolution Psychiatrique, 2018)
Résumé - Objectifs - Cet article présente l’hypothèse, issue du champ de la psychopathologie phénoménologique, de l’hyper-réflexivité schizophrénique, selon laquelle les patients schizophrènes sont pris dans l’expérimentation d’une conscience qui se retrouve contrainte d’interroger des phénomènes qui devraient aller intuitivement de soi. - Méthodes - La perspective en première personne est une démarche qualitative complétant la lecture, traditionnelle dans le champ de la psychiatrie, en troisième personne - qui consiste en l’attribution depuis une position externe de signes cliniques repérés indépendamment du ressenti exprimé par le patient. Cette perspective en première personne concentre son attention sur l’expérience subjective qu’exprime le sujet. Le discours de plusieurs patients schizophrènes a été recueilli dans le cadre d’un dispositif clinique en utilisant l’échelle EASE (Examination of Anomalous Self-Experience). Cette échelle permet l’exploration semi-structurée, d’orientation phénoménologique, d’une série de difficultés révélatrices d’anomalies de l’expérience subjective. - Résultats - En plus des phénomènes d’hyper-réflexivité, nos analyses mettent en évidence deux grandes caractéristiques de l’être-au-monde schizophrénique. D’abord une problématique du sens commun, qui pose la question de l’intersubjectivité. Ensuite l’existence d’un trouble de l’intercorporéité, les expériences d’hyper-réflexivité schizophrénique s’accompagnant d’une perte du « corps commun ». - Discussion - L’application d’une perspective en première personne dans la compréhension du vécu des patients schizophrènes, ainsi que l’intérêt porté au phénomène d’hyper-réflexivité, permettent de proposer une vision de la schizophrénie qui n’est plus réduite à une lecture déficitaire de celle-ci (sans nier cette dernière), et qui découvre non pas un affaiblissement, mais une intensification de la conscience. - Conclusions - La prise en considération de la dimension tacite de l’existence schizophrénique, telle que le suggère la psychopathologie phénoménologique contemporaine, offre de précieuses informations à la pratique clinique et suggère d’importantes perspectives de recherche associant aux designs méthodologiques conventionnels des perspectives novatrices et prometteuses. - Objectives - This paper considers the hypothesis of schizophrenic hyper reflexivity, which originates in the field of phenomenological psychopathology. It discusses the methodological context enabling these highly subjective manifestations to emerge. Starting from the seminal hypothesis developed by contemporary psychopathology that schizophrenic patients experience a form of consciousness that finds itself forced to question phenomena that should be intuitively self-evident, the idea of the present paper is to complete the usual interpretation of schizophrenia as a deficit by the hypothesis of an excessive functioning of consciousness. - Methods - The first-person perspective is a qualitative approach completing the third-person interpretation, traditional in the field of psychiatry, which consists in the attribution, from an external position, of clinical signs noted independently from the perceptions expressed by the patient. The first-person perspective focuses on the patient's subjective experience as expressed by that individual. To understand schizophrenia according to this perspective, the narratives of several schizophrenic patients were collected in a clinical setting. We used the EASE scale (Examination of Anomalous Self-Experience) for this purpose. This scale offers a phenomenologically-oriented semi-structured exploration of a set of difficulties revealing anomalies in subjective experience, considered as self-awareness disturbances. EASE was developed on the basis of self-descriptions by patients suffering from schizophrenic spectrum disorders. This tool enables the co-construction of a language between patient and clinician, focused on the patient's particular experiences and the unique phenomena he has to cope with. - Results - Alongside the hyper reflexivity phenomena, the qualitative analyses of the descriptions collected highlight two important features of schizophrenic being-in-the-world. First a common sense issue, which raises the question of inter-subjectivity and the scope for schizophrenic patients to share in a social world. Secondly, the existence of an intercorporeality disturbance, since the schizophrenic hyper reflexivity experiences are accompanied by a loss of the “common body”, the body being the scene where inter-subjectivity is played out. - Discussion - The use of the EASE scale and the application of the first-person perspective provides a relevant psychotherapeutic approach, both in the process of acknowledgement of the illness (required from the patient as well as from the clinician), and in communication with the families of schizophrenic patients. - Conclusions - The phenomenological interpretation provided by the application of a first-person perspective in the understanding of schizophrenic patients’ experiences, and the inclusion of hyper reflexivity phenomenon, suggest perspectives on schizophrenia that are no longer reduced to a mere interpretation of deficit (without denying the deficit), showing not a weakening, but a surprising intensification of consciousness.
Gesehen am 14.02.2020
Available online 24 August 2017